Current smoking habits in British IBD patients in the age of e-cigarettes. Issue 1 (21st June 2019) - Chong, Chui; Rahman, Anisha; Loonat, Khaleel; Sagar, Rebecca C; Selinger, Christian Philipp
Abstract : Background: Smoking has a detrimental effect on Crohn's disease (CD) while data on ulcerative colitis (UC) are conflicting. Smoking habits have changed dramatically in the UK due to a public smoking ban and the advent of e-cigarettes. We describe current smoking rates in patients with inflammatory bowel disease (IBD) and any effects on disease course. Methods: Self-reported smoking status was elicited in outpatients with IBD, and clinical data were extracted from patient records. Results: Of 465 patients (58% CD, 42% UC), 247 (53.1%) were ever-smokers (37.4% ex-smokers, 15.7% current smokers). Electronic cigarettes (e-cigarettes) were ever used by 28 patients (15 current users). All e-cigarette users had previously smoked cigarettes and 13 had stopped smoking completely. Patients with CD were more likely to currently smoke (21.5% vs 7.7%, p<0.001) than those with UC. Ever use of biological therapy was higher in current smokers compared with never smokers (49% vs 35%, p=0.034). The need for surgery was higher in current smokers compared with never smokers (43% vs 25%, p=0.006). The risk of CD complications during 21-month prospective follow-up was numerically higher for current smoker versus e-cigarette users (53% vs 17%, p=0.19). Compared with the general population, the proportion of current cigarette smokers (14.9% vs 15.1%) and e-cigarette users was similar in our cohort (4.26% vs 5.5%). Conclusions: Patients with IBD show similar smoking behaviour to the general population. E-cigarettes were used as replacement for cigarettes or by some as an intermediate step for smoking cessation. Larger, prospective studies are required to fully determine the effects of e-cigarettes on IBD.